Intersections of the legal system and the deaf community: from law enforcement to incarceration - Feldman, David M. (Springerbriefs in psychology behavioral criminology, 2023)
This book examines how those with disabilities, and in particular, the Deaf and hard-of-hearing, are impacted by the influence language and culture in policing, criminal law, and corrections. Frequently left out of policy making and research, almost no resources exist that can inform and aid law enforcement, legal, and correctional officials on culturally competent interactions with the Deaf and hard-of-hearing. As a result, this group is at a distinct disadvantage when dealing with law enforcement or the courts as well as being vastly underserved, which often lead to negative outcomes for the Deaf suspect/defendant/inmate as they attempt to interact with law enforcement and navigate the legal system. In a step-by-step presentation from arrest to incarceration each chapter will discuss a specific part of the legal system. As well as providing information on the topic, this book can serve as an important resource to the myriad of issues and difficulties that may be experiences by the Deaf suspect, defendant, or inmate, as well as by law enforcement officers, attorneys, and correctional officers. To illustrate these issues, previous cases of Deaf suspects, defendants, and inmates will be presented and discussed to clarify key issues and to provide a perspective of the problem. Each chapter dealing with these issues will also provide suggestions for more culturally competent interactions between the Deaf community and the legal system.